Effect of olive mill wastewaters on Scenedesmus sp. growth, metabolism and polyphenols removal. (2nd April 2021) - Dahmen‐Ben Moussa, Ines; Maalej, Amina; Masmoudi, Mohamed A; Feki, Firas; Choura, Sirine; Baccar, Nidhal; Jelail, Lobna; Karray, Fatma; Chamkha, Mohamed; Sayadi, Sami
Abstract: BACKGROUND: The three‐phase extraction process of olive oil produces highly contaminated wastewater (OMW). The elimination of this toxic by‐product is an important environmental issue that requires the development of an appropriate management solution. The cultivation of microalgae using OMW as growth medium was therefore studied using single (the culture medium was formed by 0% to 80% ultrafiltered olive mill wastewater (OMUF) or OMW added to BG11) and two‐stage strategies (microalgae were firstly cultivated in the BG11 medium. In the second stage, 40% and 80% of OMUF and OMW were added to the culture). In this work, biodegradation of OMW and subsequent extraction of lipid and antioxidant molecules was investigated as an ecofriendly method for the bioremediation and valorization of OMW. RESULTS: For two‐stage cultivation, OMUF and OMW stress enhanced the intracellular amount of polyphenol accumulated in Scenedesmus sp. and exhibited the highest 2, 2‐diphenyl−1‐ picrylhydrazyl radical (DPPH) and 2, 2'‐azino‐bis (3‐ethylbenzoline‐6‐sulfonate) radical (ABTS) scavenging ability compared with single‐stage cultivation. Moreover, the lipid profile is dominated by polyunsaturated acids. In the single‐stage cultivation, the Ch a, Ch b, carotenoid, carbohydrate and lipid content of 2.57, 7.4, 1.69, 368, and 644 g kg −1 were observed in 40% OMUF added culture, respectively, along with high biomass productivity and 58% of polyphenol removal. Moreover, the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay showed that the biomass of Scenedesmus sp. cultured on 40% OMUF did not show any toxic effect, making it an efficient strategy. CONCLUSION: The results indicate that Scenedesmus sp. is a promising microalga for the biotreatment of OMW and the extraction of bioactive metabolites. © 2021 Society of Chemical Industry.